A comparison of the reproductive performance of ablated and unablated Scylla serrata, Scylla tranquebarica and scylla olivacea broodstock. - Samaniego, Ana Lizza Duriman (2003.)
A study was done to compare the reproductive performance of sexually mature ablated and unblated Scylla Serrata, Scylla tranquebarica and Scylla olivacea. The eyestalk of the crab was unilaterally ablated to induce spawning and gonadal maturation., Thirty-two sexually mature crabs randomly selected from the wild were identified as Scylla serrata, Scylla tranquebarica and Scylla olivacea. Crabs of the same species were maintained in three 10-tonner concrete tanks filled with seawater, provided with 10-cm sand substrate and strong aeration. Eyestalk of six female S. serrata, seven S. tranquebarica females and seven S. olivacea were left intact. Survival of the broodstock, spawning, fecundity, fertilization rate and hatching were monitored. Berried crabs were transferred in 200L tanks without substrate. There was 100% water change through flow-through on a daily basis during incubation. The duration of the experiment was 3 months. Results showed that there were 50% spawning in ablated S. serrata and 25% in S. olivacea. There was only 16% spawning in unblated S. serrata and no spawning in S. olivacea. On the other hand, there was no spawning in ablated but 43% spawning in unblated S. tranquebarica. It took an average of 40 days in S. serrata for spawning to occur, 70 days in S. tranquebarica and 63 days in S. olivacea. Mean number of eggs per gram body weight (fecundity) was observed to be higher in S. serrata compared to S. olivacea. There was no trend in the survival between ablated and unblated crabs in all species. Survival ranged from 68% to 80%.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Scylla serrata; Scylla tranquebarica; Scylla olivacea